Gender differences in writing complex sentences: A case study of Indonesian EFL students - Maria Fe Suganob-Nicolau; Katharina Endriati Sukamto (Universitas Katolik Indonesia Atma Jaya, 2016)
This study investigated the Indonesian EFL students’ proficiency in writing complex sentences and explored the gender differences in their writing products. Thirty-eight (38) high school students – 19 males and 19 females – were instructed to write a narrative account of the silent movie, The Pear Film, immediately after watching it. The result of the study revealed that the students’ production of sentence complexity exhibited a sequential degree of difficulty from simple sentence (1 T-unit) to more complex sentences (2 T-units or 3 T-units). Female students had higher frequencies in producing T-units, and they also exhibited a more powerful imagination and creativity in building complex sentences. However, the males outnumbered the females in the production of lexical variety. This indicated that longer sentences are not always directly related to the breadth of vocabulary knowledge.